1981
DOI: 10.1021/bi00504a006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of globular protein secondary structure from circular dichroism

Abstract: A new method is developed in which a circular dichroism (CD) spectrum is analyzed directly as a linear combination of the CD spectra (from 190 to 240 nm) of 16 proteins whose secondary structures are known from X-ray crystallography. This avoids the dilemma encountered in previous methods of trying to define single reference CD spectra that were supposed to characterize such broad and variable classes as helix, beta sheet, beta turn, and "remainder". It also permits a more accurate and flexible analysis. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,467
2
15

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,087 publications
(1,522 citation statements)
references
References 18 publications
38
1,467
2
15
Order By: Relevance
“…CD and difference spectra were fit by nonconstrained MLR 23 using a polypeptide reference set. 24 Spectra of the individual sRz and sRz1 proteins were also fit using the CONTINLL 25,26 and CDSSTR 27 programs available on the DICHROWEB server. 28 To determine the molar ratio of sRz to sRz1 in the complex, a 10 lM solution of sRz in 10 mM sodium phosphate, 100 mM NaCl, pH 7.5, at 25 C was titrated, in 2.5 lM increments, with a stock solution of sRz1 supplemented with 10 lM sRz.…”
Section: Circular Dichroism Measurementsmentioning
confidence: 99%
“…CD and difference spectra were fit by nonconstrained MLR 23 using a polypeptide reference set. 24 Spectra of the individual sRz and sRz1 proteins were also fit using the CONTINLL 25,26 and CDSSTR 27 programs available on the DICHROWEB server. 28 To determine the molar ratio of sRz to sRz1 in the complex, a 10 lM solution of sRz in 10 mM sodium phosphate, 100 mM NaCl, pH 7.5, at 25 C was titrated, in 2.5 lM increments, with a stock solution of sRz1 supplemented with 10 lM sRz.…”
Section: Circular Dichroism Measurementsmentioning
confidence: 99%
“…For secondary structure predictions, spectra in the far-UV region (190-240 nm) were recorded at 22 C with 0.5 nm increments in a 0.5 mm quartz cell, and six scans were averaged for each spectrum. Secondary structure estimates of wild type and mutant MexR was made using DICHROWEB 33,51 and the algorithms CDSSTR, 52,53 CONTIN, 54,55 and Selcon3. 56 Thermal denaturation spectra were recorded at 210-240 nm with 5 C intervals from 15-85 C using a 0.5 mm quartz cell, 15 lM protein in 10 mM sodium phosphate buffer, pH 7.2.…”
Section: Circular Dichroism Experimentsmentioning
confidence: 99%
“…The spectrum reveals molar ellipticity minima at 208 nm and 222 nm, indicative of the presence of α-helix secondary structure. Deconvolution of the spectrum with the Contin program of Provencher and Glöckner (11) indicated that, at pH 3, apoA-V is comprised of 32 % a-helix, 33 % ß-sheet, 16 ß-turn and 18 % random coil. Thus, unlike most members of the exchangeable apolipoprotein family, apoA-V displays significant amounts of ß structure.…”
Section: Apoa-v Interaction With Phospholipid Bilayer Vesicles Of DImentioning
confidence: 99%